Differences in Self-Management of Emergency Hemodialysis Patients and Regular Hemodialysis in Chronic Kidney Disease Patients - Fransiska Diah Apriliani; Isni Lailatul Maghfiroh; Aprelia Afidatul Hanafi; M. Syukri Ghozali (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Background: Chronic kidney disease (CKD) is a global health problem where the kidneys experience progressive and irreversible dysfunction. CKD patients undergoing hemodialysis require good self-management skills to maintain therapy adherence and prevent complications. The purpose of this study was to determine the differences in self-management between emergency hemodialysis patients and regular hemodialysis patients. Assessing differences in self-management between the two groups is important because self-management skills play a direct role in fulfilling therapy and preventing complications. This study used a comparative study with a cross-sectional approach with a sample of 58 selected according to the provisions. The inclusion criteria for both groups were patients diagnosed with CKD with scheduled or emergency hemodialysis, while the exclusion criteria were patients in an unconscious state. The reason for using a cross-sectional approach was because the study only assemble data at a single point in time. This data was assemble using the HDSMI instrument and analyzed by the Mann Whitney test. As the answer showed that there were differences in self-management between emergency hemodialysis patients and regular hemodialysis patients in chronic kidney disease patients with a p = 0.000 result. Conclusion: This difference in self-management is due to the fact that regular hemodialysis patients generally have received education about fluid diet management. In contrast, emergency hemodialysis patients who arrive typically demonstrate poor self-management skills due to limited education and a lack of monitoring for signs of distress. Research findings suggest that limited education and inadequate health monitoring can contribute to the occurrence of emergencies in hemodialysis patients.